Circulating Tumor Cells as a Marker for Progression‐free Survival in Metastatic Castration‐naïve Prostate Cancer. Issue 8 (10th March 2017) - Josefsson, Andreas; Linder, Anna; Flondell Site, Despina; Canesin, Giacomo; Stiehm, Anna; Anand, Aseem; Bjartell, Anders; Damber, Jan‐Erik; Welén, Karin
Abstract : BACKGROUND: Analysis of circulating tumor cells (CTC) is a promising prognostic marker in castration‐resistant prostate cancer (CRPC). The aim of this study was to investigate CTC detection and phenotyping as prognostic biomarkers for response to primary androgen deprivation therapy (ADT) of metastatic prostate cancer (PC). METHODS: PC patients presenting with a prostate specific antigen (PSA) >80 ng/ml and/or metastatic disease, intended for ADT were enrolled in the study. CTCs were analysed for expression of PSA prostate specific membrane antigen (PSMA) and epidermal growth factor receptor (EGFR) before and three months after ADT and related to progression. RESULTS: At inclusion, 46 out of 53 patients (87%) were CTC‐positive with a sensitivity and specificity for distant metastases (M1) of 98% and 75%, respectively. In patients with M1‐disease, EGFR‐detection in CTC was an independent prognostic marker for progression‐free survival, whereas PSA and alkaline phosphatase serum levels, Gleason score, or T‐stage were not. EGFR‐positive patients had significantly shorter time to progression (5 months) compared to EGFR‐negative patients (11 months) ( P  < 0.05). CONCLUSIONS: In this explorative study, CTCs were detected in 98% of M1 patients and detection of EGFR in CTCs was strongly associated with poor outcome, which indicated that phenotypical analysis of CTC could be a promising prognostic marker of ADT‐response in castration‐naïve metastatic PC patients. Prostate 77:849–858, 2017 . © 2017 Wiley Periodicals, Inc.